2017
DOI: 10.1016/j.jcin.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of the Right Ventricular Outflow Tract Promotes Better Pulmonary Arterial Growth Compared With Modified Blalock-Taussig Shunt Palliation in Tetralogy of Fallot–Type Lesions

Abstract: RVOT stenting promotes better pulmonary arterial growth and oxygen saturations compared with mBTS in the initial palliation of Fallot-type lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 20 publications
1
49
1
9
Order By: Relevance
“…6 Quandt et al in their study comparing right ventricular outflow tract stenting with modified Blalock-Taussig shunt concluded that right ventricular outflow tract stenting promotes better pulmonary arterial growth and oxygen saturations compared with modified Blalock-Taussig shunt in the initial palliation of Fallot-type lesions. 7 Our anecdotal report augments further the indication for right ventricular outflow tract stenting in a complex cardiac morphology with a neonatal single ventricle pathophysiology (TA-IB), but should not underscore the risk of such a challenging procedure. Since the ductus was closed in our case, the options were to consider either surgery or right ventricular outflow tract stenting.…”
Section: Discussionmentioning
confidence: 68%
“…6 Quandt et al in their study comparing right ventricular outflow tract stenting with modified Blalock-Taussig shunt concluded that right ventricular outflow tract stenting promotes better pulmonary arterial growth and oxygen saturations compared with modified Blalock-Taussig shunt in the initial palliation of Fallot-type lesions. 7 Our anecdotal report augments further the indication for right ventricular outflow tract stenting in a complex cardiac morphology with a neonatal single ventricle pathophysiology (TA-IB), but should not underscore the risk of such a challenging procedure. Since the ductus was closed in our case, the options were to consider either surgery or right ventricular outflow tract stenting.…”
Section: Discussionmentioning
confidence: 68%
“…Complications associated with interventional procedures are related to pre-exis- for RVOT stenting compared to 4.9% for modified Blalock-Taussig shunt. 44,45 The major complications related to this procedure are perforation of the RVOT and hemopericardium, damage of the tricuspid valve apparatus, stent dislodgement into the right ventricle, stent embolization into the aortic arch followed by moderate to severe aortic valve regurgitation, or stent thrombosis. [44][45][46][47][48][49][50][51][52][53]…”
Section: Results and Complicationsmentioning
confidence: 99%
“…Было продемонстрировано преимущество стентирования ВОПЖ, проявляющееся в виде значимо лучшей динамики Z-score правой и левой ЛА после выполнения вмешательства, что также отразилось на более выраженном увеличении сатурации артериальной крови кислородом. При этом период до проведения радикальной коррекции ТФ был значимо меньше у пациентов после стентирования ВОПЖ при сравнении с аорто-легочным шунтированием Блелока-Тауссига [6].…”
Section: Discussionunclassified